Hubungan antara Modal Kerja dan Profitabilitas: Studi Perusahaan Manufaktur di Indonesia yang Terdaftar di BEI - Muhammad Faisal Akbar Ibrahimy; Agung Juliarto (Diponegoro Journal of Accounting, 2018)
Working capital and profitability are important factors for entity. If one of them has a disturbance it could affect the company’s operational. This research use manufacturing company registered in ICMD for year 2012-2015. Independent variable used in this research cash conversion cycle (CCC) and CCC2. Control variables used is size,leverage, dan sales. For variable dependent use profitability representated by ROA. To analyse the relationship between independent, control dan dependent, writer used descriptive, classical assumption, liniear regression, correlation coeffisien, determination coeffision, f and t test. Based on analytical statistic of coeffisient of determination test indicated that there is no influence between independent variable which is representated by CCC and CCC2 to dependent variable profitability representated by ROA. The result show found no connection between working capital and profitability.